Effect of Cellulosic Material and Weave Design on Comfort Performance of Woven Fabrics - Muhammad Toqeer Riaz; Muhammad Imran Khan; Khubab Shaker; Yasir Nawab; Muhammad Umair (Journal of Natural Fibers, 2023)
Availability, simplicity of processing, biodegradability, sustainability, and compatibility with human skin in terms of moisture management and temperature regulation, cellulosic fibers are preferred for clothing. In this study four (04) different cellulosic yarns (cotton, bamboo, viscose, and tencel) and two weave designs (1/1 plain and 2/2 warp rib) were used to develop eight (08) woven fabrics with equal thread densities, and their volume porosity %, air permeability, thermal resistance, water vapor permeability index, and moisture management properties were compared. The results showed that tencel fabrics showed the highest water vapor permeability index and overall moisture management capability (OMMC) values, whereas cotton fabrics had the highest values of volume porosity %, air permeability, and thermal resistance. Furthermore, the 2/2 warp rib weave design showed higher values of volume porosity %, air permeability, and thermal resistance in comparison with 1/1 plain woven fabrics, while the water vapor permeability index and OMMC values were higher in 1/1 plain woven fabrics. Moreover, the statistical significance of both factors (cellulose material and weave design) on different results was also analyzed.